Exosomal MiR-4261 mediates calcium overload in RBCs by downregulating the expression of ATP2B4 in multiple myeloma - Bian, Sicheng; Zhang, Xialin; Lin, Leilei; Sun, Lili; Guo, Zhibo; Pan, Jie; Cui, Jiangxia; Yao, Hanbing; Xu, Jing; Hao, Zhuanghui; Wang, Yuzhu; Tong, Liguo; et al. (Frontiers in Oncology, 2022)
Background: The hypercalcemia induced by multiple myeloma (MM) affects the biological functions of excitable and non-excitable cells. But the regulatory effect of red blood cells (RBCs) on calcium in hypercalcemia is still not fully understood. Methods: 113 patients with MM osteolytic lesions were studied retrospectively. Flow cytometry and atomic absorption spectroscopy were used to detect calcium content. Immunofluorescence and Western blot were investigated the expression of protein. Using GEO and miRNA databases to screen miRNAs. Exosome miR-4261 migration was investigated by Transwell assay. Dual-luciferase assays confirmed the targeting relationship between miR-4261 and ATP2B4. An RBC oxidative stress model was constructed, omega-Agatoxin IVA was used to study the role of plasma membrane Ca2+-ATPase 4 (PMCA4) in RBCs. Results: The results showed that MM RBCs have calcium overload, and the level of serum calcium increased as the number of RBCs decreased. The expression of PMCA4 in MM RBCs was significantly lower than that of normal RBCs. And the exosome miR-4261 produced by MM cells could be transferred to RBCs to downregulate the expression of ATP2B4. Conclusions: Studies have confirmed that RBCs experience calcium overload in MM with osteolytic lesions, which is related to the downregulation of ATP2B4 by MM exosome miR-4261.